DEVELOPMENT OF INTERNATIONAL RELATIONS OF UZBEK MIGRANTS WITH FOREIGN COUNTRIES - Alisher Mirkholdorov (American Journals, 2025)
This is in the article. From Uzbekistan labor migrants foreign countries with international connections in the development of place and role highlighted. Today on that day external labor migration Uzbekistan foreign policy economic and social from the point of view important in the direction has become.
Keywords: Labor, migration, international relations, diasporas, Uzbekistan, abroad, fifty jobs, suppliers, foreign policy, investments, transnational cooperation.